PARADIGMA BARU MANAJEMEN SUMBERDAYA MANUSIA - Bayu Airlangga Putra (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2002)
The field of human resources (HR) management is expected to play more strategic roles in the global context of business. Consequently, a new paradigms are needed to be internalized into the mind of HR professionals. Unfortunately, it seems that not all, if not most, of HR pofessionals have those new paradigms, causing a lot of people perceive HR department as being stagnant. This article seeks to examine the historical roots that have shaped HR departments and HR professionals into their recent form. Then, it tries to identify the challenges faced by HR professionals and what can be done to anticipate those challenges.Among the proposed solutions are learning process and entrepreneurship development. Finally, this article also discusses the career prospect in the field of HR management.